PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM MEREK AQUA SERTA IMPLIKASINYA TERHADAP CITRA MEREK DI FAKULTAS EKONOMI UNIVERSITAS BOROBUDUR - Yolanda Yolanda; Darmanitya Harseno Wijanarko (Fakultas Ekonomi Universitas Borobudur, 2018)
This study aims to examine and analyze the influence of promotion and product quality on purchasing decisions Aqua brand water and its implications on brand image. The data used in this study are primary data taken from the responses of questionnaires by students of the University of Borobudur faculty of economics management study program. The method of data processing using path analysis with the aid of SPSS version 23. The ststistic test in this research use fitness test model (goodness of fit test).The result of the research shows that promotion has positive and significant effect directly or indirectly through brand image to purchasing decision, product quality have positive and significant influence directly or indirectly through brand image to purchasing decision and brand image have positive effect directly to purchasing decision . Keywords: Promotion, product quality, brand image, purchase decision.